(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
Arabic media language is distinguished from other media languages by its unique stylistic features.This article analyzes the main genres of written speech in the newspaper-journalistic style: the journalistic article and the newspaper report. While the purpose of a journalistic article is to persuade, to prove something, and to evoke a specific reaction–not only through the logical construction of an utterance but also through the power of emotional impact–the newspaper report provides only essential and core information.